A Study of Transvaginal Ultrasonography in diagnosis of Endometrial Pathology in abnormal Uterine Bleeding - Syeda Ali, Faryal Akhtar, Maham Munir Awan, Mustafa Ali Siddiqui, Hammad Ahmad Saqib, Mahwish Zahra, M.M. Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the utility of transvaginal ultrasonography (TVS) in assessing the pathologic causes of Abnormal Uterine Bleeding (AUB). Methodology: The descriptive study was conducted in Gynecology Unit Nishtar Hospital Multan from July-2021 to July-2022. A total of 80 women with diagnosis of AUB were recruited. Every patient with an AUB underwent TVS. The thickness of the endometrium, its echogenicity, the size of the uterus, and any uterine or adnexal abnormality observed. Results: Mean age was 46.16±9.50 years with range 25-60 years. Regarding menopausal status, 35 (43.75%) females were pre-menopausal and 45 (56.25%) were post-menopausal.On TVS findings, normal proliferative endometrium was found in 26 (32.5%) cases, endometrial polyps in 22 (27.5%) cases,myomas in 12 (15.0%) cases, hyperplasia in 12 (15.0%) cases, endometrial atrophy in 5 (6.25%) cases, and suspicious looking endometrium in 3 (3.75%) cases. Practical Implications: The study is very useful, knowledgeable, cost efficient and cost effective. Conclusion: TVS is a safe, rapid and cost-effective modality for the diagnosis of endometrial pathologies. Endometrial polyps, myomas and hyperplasia are common cause of AUB. Keywords: Transvaginal ultrasonography, abnormal uterine bleeding, polyps.